Mangrove Species Diversity in Coastal Village swollen Banyuwangi Regency - Yanuar Rustrianto Buwono (Airlangga University, 2019)
The Bengkak coastal area is one of the coastal areas which is a marine fishery activity with a natural mangrove ecosystem of ± 9 ha bordered by reed mangrove and opposite to TN West Bali mangrove. Environmental pressure with the presence of human activities such as the extraction of mangrove wood causes the growth and development of mangroves not optimal and affects the potential of mangrove ecosystems so research needs to be done to determine the diversity of mangrove ecosystems on the coast of Bengkak Village, Banyuwangi District. Observations in the whole mangrove ecosystem have low species diversity criteria, namely H 'ranging from 0.20 - 0.67 and dominated by A. marina species from the families Avicenniaceae and R. mucronata from the family Rhizophoraceae. While the density of species in all observation stations found that mangrove stands ranged from 967 - 82,000 Ind / Ha. The density of A. marina mangrove vegetation was identified as the highest in the seedling phase of 7,500 Ind / Ha, the sapling phase was 74,000 Ind / Ha and the tree phase was 567 Ind / Ha. The lowest type of R. mucronata was identified in the seedling phase of 5,000 Ind / Ha, sapling phase of 8,000 Ind / Ha and tree phase of 400 Ind / Ha. Environmental factors in the form of nutrients such as leaf litter and the quality of the aquatic environment also influence the growth and development of mangrove ecosystems. environmental conditions in the mangrove zone have the texture of sandy soil and sandy mud, temperatures range from 23 - 33 °C, pH ranges from 7 and salinity ranges from 23 - 36